Molinist Gunslingers Redux: A Friendly Response to Greg Welty - Keathley, Kenneth D. (2018)
Philosopher Greg Welty contributed a chapter entitled ‘Molinist Gunslingers: God and the Authorship of Sin’, to a book devoted to answering the charge that Calvinism makes God the author of sin (Calvinism and the Problem of Evil). Welty argues that Molinism has the same problems as Calvinism concerning God’s relationship to sin, regardless of what view of human freedom Molinism may affirm. The Molinist believes that God generally uses his knowledge of the possible choices of libertarianly free creatures in order to accomplish his will. (This knowledge is typically categorized as residing within God’s middle knowledge.) But affirming libertarian freedom for humans, he argues, does not help in dealing with the question of God’s relationship to evil. Therefore, Molinism is no better than Calvinism, at least concerning this issue. In response to Welty, (1) I agree with him that Molinism does not have a moral advantage over what he calls ‘mysterian, apophatic’ Calvinism, but Molinists don’t claim that it does, and (2) I argue that, contra Welty, Molinism indeed does have a moral advantage over the Calvinist versions that do employ causal determinism. Welty does not take ‘intentions’ into consideration in his argument, and this is a serious flaw. In the libertarian model of Molinism, intent originates in the doer of evil. However, in the compatibilist model of causal determinism, ultimately God implants intent. Thus, adherents of causal determinism have difficulty not laying responsibility at the feet of God.
Keywords: Molinism -- Calvinism -- determinism -- libertarianism -- problem of evil